2013
DOI: 10.1017/s1355617713000015
|View full text |Cite
|
Sign up to set email alerts
|

Can Risk-Taking Be an Endophenotype for Bipolar Disorder? A Study on Patients with Bipolar Disorder Type I and Their First-Degree Relatives

Abstract: Risk-taking behavior and impulsivity are core features of bipolar disorder. Whether they are part of the inherited aspect of the illness is not clear. We aimed to evaluate risk-taking behavior as a potential endophenotype for bipolar disorders, and its relationship with impulsivity and illness features. The Balloon Analogue Risk Task (BART) and Barratt Impulsiveness Scale-11 (BIS-11) were used to assess risk-taking behavior and impulsivity respectively in 30 euthymic bipolar I patients (BD), their 25 asymptoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 40 publications
2
22
3
Order By: Relevance
“…However, specificity of impulsivity to BD is questionable as it shows shared genetic liability with SCH and major depressive disorder [30] and requires further studies. Risk-taking behavior may also be a potential endophenotype and predictor of BD [32, 33]. …”
Section: Resultsmentioning
confidence: 99%
“…However, specificity of impulsivity to BD is questionable as it shows shared genetic liability with SCH and major depressive disorder [30] and requires further studies. Risk-taking behavior may also be a potential endophenotype and predictor of BD [32, 33]. …”
Section: Resultsmentioning
confidence: 99%
“…However, the results do not show the underlying causes that link them. Within BD, relatively few relatives meet full diagnostic criteria for the disorder, but many experience high levels of impulsivity when compared to healthy controls ( Hıdıroğlu et al, 2013 ). One possibility is that lack of inhibitory control in relatives is a marker of familial contexts which are prone to maltreatment behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Dysmodulation of reward and emotion processing and emotion regulation, including failure to down-regulate emotional reactivity to positive stimuli, may represent a specific endophenotype of BD given evidence of co-segregation of these traits in families at risk for BD. Behavioural studies have found that BD patients and URs compared to healthy controls showed a reduced ability to modulate risk taking in the face of certain types of stressors (Hidiroglu et al 2013 ) and increased trait impulsivity and impulsive decision-making (Wessa et al 2015 ).…”
Section: Cognitive Emotional and Reward Processing Endophenotypesmentioning
confidence: 99%